Sex Differences in Stroke Incidence, Prevalence, Mortality and Disability-Adjusted Life Years: Results from the Global Burden of Disease Study 2013 - Barker-Collo,S; Bennett,DA; Krishnamurthi,RV; Parmar,P; Feigin,VL; Naghavi,M; Forouzanfar,MH; Johnson,CO; Nguyen,G; Mensah,GA; Vos,T; Murray,CJL; et al. (Neuroepidemiology, 2015)
BACKGROUND: Accurate information on stroke burden in men and women are important for evidence-based healthcare planning and resource allocation. Previously, limited research suggested that the absolute number of deaths from stroke in women was greater than in men, but the incidence and mortality rates were greater in men. However, sex differences in various metrics of stroke burden on a global scale have not been a subject of comprehensive and comparable assessment for most regions of the world, nor have sex differences in stroke burden been examined for trends over time. METHODS: Stroke incidence, prevalence, mortality, disability-adjusted life years (DALYs) and healthy years lost due to disability were estimated as part of the Global Burden of Disease (GBD) 2013 Study. Data inputs included all available information on stroke incidence, prevalence and death and case fatality rates. Analysis was performed separately by sex and 5-year age categories for 188 countries. Statistical models were employed to produce globally comprehensive results over time. All rates were age-standardized to a global population and 95% uncertainty intervals (UIs) were computed. FINDINGS: In 2013, global ischemic stroke (IS) and hemorrhagic stroke (HS) incidence (per 100,000) in men (IS 132.77 (95% UI 125.34-142.77); HS 64.89 (95% UI 59.82-68.85)) exceeded those of women (IS 98.85 (95% UI 92.11-106.62); HS 45.48 (95% UI 42.43-48.53)). IS incidence rates were lower in 2013 compared with 1990 rates for both sexes (1990 male IS incidence 147.40 (95% UI 137.87-157.66); 1990 female IS incidence 113.31 (95% UI 103.52-123.40)), but the only significant change in IS incidence was among women. Changes in global HS incidence were not statistically significant for males (1990 = 65.31 (95% UI 61.63-69.0), 2013 = 64.89 (95% UI 59.82-68.85)), but was significant for females (1990 = 64.892 (95% UI 59.82-68.85), 2013 = 45.48 (95% UI 42.427-48.53)). The number of DALYs related to IS rose from 1990 (male =